MAKNA DAN FUNGSI BEBERAPA STEMPEL DAN MATERAI KUNA DARI ACEH DAN RIAU - Ery Soedewo (Berkala Arkeologi Sangkhakala, 2006)
Stamps and Seals are tools that used as a decisive validity of issued by the empire, institution, trading house and individual. Its existence was the evidence of the authority legitimation, as a symbol that there was a confermed a nobility’s degree upon a foreigner and also showed the changing of the bureaucracy structure because of the new political power.